2015
DOI: 10.1038/srep18081
|View full text |Cite
|
Sign up to set email alerts
|

No association between HPV positive breast cancer and expression of human papilloma viral transcripts

Abstract: Infectious agents are thought to be responsible for approximately 16% of cancers worldwide, however there are mixed reports in the literature as to the prevalence and potential pathogenicity of viruses in breast cancer. Furthermore, most studies to date have focused primarily on viral DNA rather than the expression of viral transcripts. We screened a large cohort of fresh frozen breast cancer and normal breast tissue specimens collected from patients in Australia for the presence of human papilloma virus (HPV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…Koilocytes are HPV infected epithelial cells with characteristic haloes surrounding a small nucleus. HPV E6 and E7 oncoproteins have been identified in breast cancer ( 138 ), however, there is a low level of transcription of these oncoproteins ( 168 ).…”
Section: High-risk Human Papilloma Viruses and Breast Cancermentioning
confidence: 99%
“…Koilocytes are HPV infected epithelial cells with characteristic haloes surrounding a small nucleus. HPV E6 and E7 oncoproteins have been identified in breast cancer ( 138 ), however, there is a low level of transcription of these oncoproteins ( 168 ).…”
Section: High-risk Human Papilloma Viruses and Breast Cancermentioning
confidence: 99%
“…However, a small number of investigations could not find HPVs in breast cancer and normal mammary tissues ( 106 108 ). In this regard, E6/E7 onco-proteins of HPVs have been identified in breast cancer ( 109 ); though, there is a low level of transcription of these onco-proteins ( 110 ). Meanwhile, it has been reported that the presence of HPVs in breast cancer is associated with more aggressive phenotype ( 9 , 82 , 103 , 111 ).…”
Section: Ebv/hpvs Interaction and Emt In Human Cancermentioning
confidence: 99%
“…This is in contrast to the up to sixfold increase in prevalence of HPV associated cervical cancer in similar patients. Transcription from HPV DNA to RNA in HPV-associated breast cancer has not been identified by some investigators ( 47 ). However, a very low prevalence of HPV transcripts has been identified in the TCGA series of breast tumors ( 10 ).…”
Section: Introductionmentioning
confidence: 99%